1.9 A structure of the therapeutic antibody CAMPATH-1H fab in complex with a synthetic peptide antigen. - James, L; Hale, G; Waldmann, H; Bloomer, A; Waldman, H (1999)
CAMPATH-1 antibodies have a long and successful history in the treatment of leukaemia, autoimmune disease and transplant rejection. The first antibody to undergo "humanisation", CAMPATH-1H, permits treatment with limited patient anti-globulin response. It recognises the CD52 antigen which is a small glycosylphosphatidylinositol(GPI)-anchored protein expressed on lymphocytes and mediates cell depletion. We present the 1.9 A structure of the CAMPATH-1H Fab complexed [corrected] with an analogue of the antigenic determinant of CD52. Analysis of the CAMPATH-1H binding site reveals that in contrast to most antibodies CDR L3 plays a dominant role in antigen binding. Furthermore CDR H3, which is essential for effective antigen recognition in most antibodies, participates in only two main-chain interactions in CAMPATH-1H. The CAMPATH-1H binding site is highly basic; ionic interaction with the enthanolamine phosphate of the CD52 GPI anchor has long been hypothesised to be important in antigen binding. The structure reveals a number of important specific ionic interactions, including Lys53H but not Lys52bH as had previously been suggested. Prolonged treatment with CAMPATH-1H can lead to patient anti-idiotype responses which may be exacerbated by the unusually high number of basic residues in the antibody. This suggests that a strategy where redundant basic residues are replaced with neutral counterparts may be effective in further reducing the immunogenicity of this versatile and widely used antibody.